Reliable air to ground communications for low altitude unmanned aerial vehicles - Saraiva, Tiago Martins (2016)
Currently the use of Unmanned Aerial Vehicles (UAVs) for civilian purposes is growing exponentially, whereas in the past it was a technology used only for military objectives. There is an array of applications that can be accomplished with the use of this technology, such as making aerial films on a low budget, coast surveillance, parcel deliverance, and many other applications. However, in a civilian environment, these UAVs systems are typically controlled with a line-of-sight (LOS) technology such as Radio Control (RC), which limits the range that the system can be operated. Therefore, the main objective of this thesis is to study the use of mobile wireless networks as a viable replacement of RC control, to have a full control of the vehicle, providing then an extended mobility to the operator and vehicle. To accomplish this an Unmanned Vehicle System (UVS) was developed in order to monitor and provide the user with the ability to control several drones, such as UAVs and Unmanned Ground Vehicles (UGVs), using mobile networks. The user can operate the vehicle using a Remote Ground Station (RGS) that provides full control of the vehicle, with an android mobile application making it accessible, with no associable costs. On the vehicle a Raspberry PI (RPI) is attached, that receives and handles the information to control the drone and provides the user with a live stream that allowing sight from the Point of View (POV) of the drone, enabling responsibility to the RPI to communicate between the drone and the user. With this approach the system is completely independent from the RC technology, allowing the user to control the vehicle without the need of physical presence on the side, creating a vast new array of uses for this kind of technology.